P-84 Advance care planning for patients with heart conditions in a multiethnic south east asian cohort: Impact of nurse navigator. (1st September 2015) - Lau, Cindy SL; Wong, Jane CQ; Tan, SH; Tan, BC; Ng, CSH; Lim, SM; Wong, G; Sim, KLD
Abstract : Background: Our institution has initiated inpatient advance care planning (ACP) programme for heart failure patients in 2013. Enrollment rate has been low. Aim: Expansion of ACP programme to arrhythmia and myocardial infarction (MI) patients besides heart failure (HF) with support from nurse navigators to increase enrollment. Methods: Patients hospitalised for MI were approached by ACP trained nurse navigators from 1 st October 2014 to 30 th November 2014, while patients with arrhythmia were approached by ACP coordinators from 1 st July 2014 to 30 November 2014. Heart failure patients were approached by ACP coordinators from 1 st June 2013 to 30 th November 2014. Results: 112 (5.8%) patients were enrolled from a total screening of 1943 patients. The mean age of patients was 63.9 years and majority was male (73.2%). Ethnic distribution: Chinese 83%, Malay 8%, Indians 7%. 7 out of 61 MI patients were enrolled by the nurse navigators. 8 out of 273 arrhythmia patients and 97 out of 1609 HF patients were enrolled by ACP coordinators. Enrollment rates for MI 11.5%, arrhythmia 2.9%, HF 6.0%. Discussion: There is a significant increase in enrollment rate of ACP programme after the engagement of nurse navigators' support. During the patient's hospital stay, rapport and trust have built up among the patient, caregiver and nurse navigator. This resulted in patient being more open and able to accept ACP when approached by nurse navigator. Conclusion: Healthcare providers who have built up a rapport with patients play an important role in advocating ACP programme.